UNDERSTANDING PROFILE FROM THE PHILOSOPHY, PRINCIPLES, AND CHARACTERISTICS OF RME - Julie, Hongki; Suwarsono, St.; Juniati, Dwi (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2014)
The aim of this study is to create understanding profiles of elementary school teachers whoÃ‚Â have been and have not been following the workshop PMRI, before and after they learned theÃ‚Â learning resource about philosophy, principles, and characteristics of realistic mathematicsÃ‚Â approach. This type of research used in this study is a combination of qualitative research andÃ‚Â developmental research. The results shown in this paper is the understanding profile of onesubject who is an elementary school teacher. Research subjects involved in the trial for the firstÃ‚Â task, the learning resource, and second task are six persons, which consists of three PGSDÃ‚Â students who are working on the final project, and three elementary school teachers.Keywords: Understanding Profile, Realistic Mathematics Education (RME), the RealisticÃ‚Â Mathematics Education Learning Resource.Ã‚Â DOI: http://dx.doi.org/10.22342/jme.5.2.1499.148-159